Factors Influencing Mortality of Thoracic Aortic Surgery in The Third World Country - Diansari, Rienna; Aligheri, Dicky; Herlambang, Bagus; Wicaksono, Sony Hilal; Yaniarti, Dian; Alkatiri, Amir Aziz; Andriantoro, Hananto; Adiarto, Suko; Mendel, Brian (The Indonesian Heart Association, 2023)
Background: A prominent increase of overall global death rate of aortic disease is seen on developing country, with South-east Asia having the highest increase of 41%. Lack of identification and prompt management of the diseases in conjunction with lack of facilities in third world countries that could perform aortic surgery made the procedure more complex when the patients admitted to tertiary hospitals Methods: The data was obtained through medical record of patients underwent thoracic aortic surgery from 2018 to 2021 in National Cardiovascular Center Harapan Kita (NCCHK). One-year and 3-year survival analysis was obtained through phone calls and digital messages. Statistical analysis was done to investigate the impact of surgical complexity as the main predictor and other variables on primary (in-hospital mortality) and secondary (mid-term survival) outcome. Results: A total of 208 patients were included in the analysis; 157 (75,5%) underwent complex surgery, and 51 (24,5%) underwent non-complex surgery. In-hospital mortality was similar across 2 groups (23,6% vs 13,7%; p = 0,1240). On multivariable analysis, malperfusion syndrome (OR 3,560; p = 0,002), CPB duration > 180 minutes (OR 4,331; p = 0,001), and surgical priority (urgent OR 4,196; p = 0,003; emergency OR 10,879; p = 0,001) were identified as independent predictor of in-hospital mortality. Cox regression identified diabetes (HR 4,539; p = 0,025) and emergency procedure (HR 9,561; p = 0,015) as independent predictors for 1-year mortality, and diabetes (HR 3,609; p = 0,004), aortic dissection (HR 2,795; p = 0,029), and maximum aortic diameter (HR 1,034; p = 0,003) for 3-year mortality. Surgical complexity was not associated with early and mid-term mortality. Conclusions: In patients undergoing thoracic aortic surgery, surgical complexity was not associated with early and mid-term survival. Early and mid-term survival was largely determined by patient comorbidities and intra-surgery factors.This article has a related Erratum.